PENGELOLAAN SEKOLAH INKLUSI: STUDI MULTI SITUS PADA SEKOLAH ISLAM DI JAWA TIMUR - akhmad nurul kawakip; Muhammad Islahul Mukmin; Selly Chandra Ayu; Abd Qadir Muslim (STAI Ma'had Aly Al-Hikam Malang, 2023)
An inclusive school is a school concept that consciously strives to guarantee children's rights and protection for children with special needs to get adequate and responsible access to education. Therefore, in practice, it refers to the principles of good management. The learning process is based on children's needs, a conducive learning climate, a supportive classroom atmosphere, and the priority of fulfilling children's learning rights. This paper examines the management of inclusive schools in Islamic schools in East Java. The aims of this research are: (1). explore forms of inclusive school policies in Islamic schools in East Java; (2). Describe the implementation of the management of inclusive children's schools in Islamic schools in East Java. Researchers used a qualitative approach with a multi-site research type. Data collection techniques consist of observation, interviews, and documentation. Data analysis with three stages; the first stage is data reduction, data presentation, and triangulation. The results of the study show: (1.) The form of policies implemented in the process of managing inclusive children's schools in Islamic schools in East Java is based on the four pillars of the principles of inclusive children's schools, namely non-discrimination, the best interest for children's growth, respect for children and values beliefs originating from religious teachings; (2.) The implementation of the management of inclusive children's schools begins with the stages of situation analysis, equalization of perceptions, organization and formation of a program implementation team.